Assessment of population exposure dose resulted from liquid discharges of Belarusian NPP in normal operation mode - Nikalayenka, Alena; Rozdyalouskaya, Larisa; Huseinava, Dziyana; Kliaus, Viktoryia (Journal of the Belarusian State University. Ecology, 2023)
Radiation safety of the population from liquid discharges of the Belarusian NPP (hereinafter – BelNPP) into surface water bodies is considered to be ensured if the exposure dose to the population due to the discharges does not exceed the value of the Dose Constraint (hereinafter – DC) established by the sanitary norms and rules for ensuring radiation safety: 50 μSv/year. If there are prerequisites for the possibility of reducing the specified DC standard, it can be revised by decision of the state sanitary supervision institutions based on estimates of annual effective doses to the population (hereinafter – referred to as YED) for a certain period of NPP operation. The purpose of the study was to consider the rightfulness of the established value of the DC standard by comparing it with the calculated values of the YED of the population from the design and predictive actual liquid discharges of the BelNPP after the commissioning of the plant. As model parameters for predictive estimates, data on actual liquid discharges from NPP – analogues of the BelNPP with a VVER-1200 reactor were used. The article presents the results of the assessment and analysis of the YED from the design and predictive actual liquid discharges of the BelNPP through all exposure pathways. It is shown that the predictive estimates of the actual YED of the population are comparable with the design YED from BelNPP discharges into the Viliya River and do not exceed 22 % of the corresponding DC standard. The remaining reserve of 78 % is sufficient to reliably ensure compliance with the DС standard for public exposure from liquid radioactive discharges of the BelNPP, including after the commissioning of the second power unit. At least 80 % of the YED of the population from liquid discharges of the BelNPP into the Viliya River will be formed due to internal irradiation, to a large extent from the consumption of fish caught in the river. External exposure of the population from liquid discharges of the BelNPP occurs mainly when staying on the beach, its contribution to the total YED from discharges does not exceed 20 %. The list of the main dose-forming radionuclides was determined and the necessity of mandatory control of the volumetric concentration of radionuclides 131I, 60Co, 58Co, 54Mn, 90Sr in waste waters of the BelNPP was substantiated.